Smart thermal comfort system: a development of the fundamental control algorithm - Abdul Shukor, Shazmin Aniza (2004)
This paper reports on the development of the fundamental algorithm for a smart thermal comfort system. Using Predictive Mean Vote (PMV) as a means of measuring thermal comfort, this system would able the user to define their own expression towards the surroundings, from slightly warm to slightly cold. Here, the operator only needs to insert its respective value ofPMV (ranging from -1 to + 1) and the system will generate the compressor and fan of the air conditioning system so that it will create a thermally comfortable environment, based on the operator's desires. This differentiates the system with the conventional air conditioning system where the operator needs to set separately fan speed and degree of cooling. The PMV value here will be calculated as input instead of the normal PMV equation where these values depend on the air temperature, relative humidity and air velocity. All these parameters values are set from the standard range allowed by the ISO 7730 of thermal comfort at a workplace for sedentary activity. Since previous researches use PMV as the output value, the help of Microsoft Excel is used to obtain air temperature and air velocity for respective values ofPMV. Finally, the fundamental stage for experimentation step is implemented by building a working region in allowing the PID (Proportional, Integrative, Derivative) controller to control its duty cycle.